Enantioselective cellular localisation of europium(iii) coordination complexes - Frawley, Andrew T. (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
The selective mitochondrial localisation of the Λ enantiomer of three different emissive europium(iii) complexes in NIH 3T3 and MCF7 cells contrasts with the behaviour of the Δ enantiomer, for which a predominant lysosomal localisation was observed by confocal microscopy. In each case, cell uptake occurs via macropinocytosis.